Key technologies of robotic arm motion control based on compound control and improved SCSO - Kuo Hu (PLoS ONE, 2025)
As modern industrial automation advances towards intelligence and flexibility, robotic arms are widely used in precision manufacturing, intelligent assembly, and medical surgery. To meet the high-precision motion control demand, this study proposes a robotic arm motion control technology integrating composite control and an improved sandcat swarm optimization algorithm. The algorithm is enhanced by introducing the Iterative chaotic iterative mapping and sparrow warning mechanism. The composite control strategy combines visual guidance with BP-PID control. Experimental results show Joint 1 has an average angle of about 50° and an average angular velocity of 0°/s. Joint 2 has an angle of about −80°, with an M-shaped angular velocity curve and large angular acceleration fluctuations, reaching a minimum angular jerk of −90/s³. Joint 3 has an angle of approximately 0°, with a W-shaped angular velocity curve and a maximum angular acceleration of 17°/s². The findings indicate the proposed technology accurately matches the kinematic and dynamic characteristics of robotic arm movements, ensuring precise joint motion trajectories and effectively suppressing shocks and vibrations. This research offers new ideas and methods for robotic arm motion control technology, with significant theoretical and practical value.